Molecular Characterization of Antibacterial Resistant Salmonella Isolated from Food Sources in Palestine - جناجرة, مجد أحمد محمد (An-Najah National University, 2018)
Introduction: Antibiotics resistance is an escalating health concern all over the world. The mis- and over-use of the antibiotics is not only noticed in human but also through the food chain. As one of the main food-borne pathogens; Salmonella is inclined for transferring the antibiotic resistance determinants. Currently, Salmonella genomic island 1 (SGI 1) and integrons are the most commonly studied determinants. Materials and Methods: A total of 128 Salmonella isolates from different sources, mainly food samples, in the Palestinian market were collected and provided by Ministry of Health central lab and the Analysis, Poison Control and Calibration Center. Antibiotic susceptibility of the isolates was determined by disc diffusion method. Polymerase chain reaction (PCR) was used to detect class 1 and 2 integrons, as well as SGI 1. Sequencing was used to confirm the SGI1 and integrons positive isolates. Antibiotic resistance profile varied among the isolates that showed multi-drug resistant (MDR) isolates. Rustles: Molecular characterization revealed that most of the isolates harbored class 1 integron with varied gene cassettes. Class 2 integron and SGI1 were detected in few isolates. Interestingly, antibiotic resistance profile is highly variable at molecular level in correlation to its phenotypic characterization. Conclusion: Antibiotic resistance determinants in Salmonella isolated from the different food sources arises the alarm for their direct role as a food-borne pathogen. Moreover, the possibility to transfer the antibiotics resistance determents horizontally that may be inclined indirectly in the super bug theory. The surveillance and monitor of the prevalence of antimicrobial resistance genes from other bacterial isolates and the antibiotics usage need strict protocols to control the emergence of the MDR bacterial isolates.
الوصف الجزيئي لمقاومة المضادات الحيوية في بكتيريا السالمونيلا المعزولة من مصادر غذائية في فلسطين